The double bind : a novel - Bohjalian, Christopher A. (New York : Vintage Books, 2008)
Working at a homeless shelter, Laurel Estabrook encounters Bobbie Crocker, a man with a history of mental illness and a box of secret photos, but when Bobbie dies suddenly, Laurel embarks on an obsessive search for the truth behind the photos
Keywords: Women college students -- Fiction; Photographers -- Fiction; Mentally ill -- Fiction